Implementasi Merdeka Belajar Dalam Mata Pelajaran Pendidikan Agama Islam Untuk Meningkatkan Sikap Religius Siswa - Basri, Junaidin; Salamudin, Ceceng; Azizah, Umi (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This research stems from societal and cultural phenomena, namely youth violence, trends towards casual sex, and the abuse of narcotics and other addictive substances. Addressing these moral issues among adolescents, the government has introduced the "merdeka belajar" curriculum, allowing for customized learning to meet students' desires and needs. The objective of this qualitative descriptive study is to examine the implementation of the "merdeka belajar" curriculum in Islamic Education to enhance students' religious attitudes at SMPIT Al-Masduki Tarogong Kidul. Data was collected through observation, interviews, and documentation. The findings reveal that: 1) SMP IT Al-Masduki offers various programs to enhance students' religious intelligence, including tahfidz al-Qur'an specialization, leadership skills training, international communication skills training, and character formation and values education programs. 2) The "merdeka belajar" curriculum at SMP IT Al-Masduki supports a talent and interest-based approach in learning, fostering flexibility and focusing on essential content and character development. 3) The use of the "merdeka belajar" curriculum in enhancing students' religious attitudes in Islamic Education at SMP IT Al-Masduki integrates national and international curricula. The implemented aspects of students' religious attitudes at SMP IT Al-Masduki encompass beliefs, worship practices, spiritual understanding, knowledge acquisition, and practical application.  Keywords: Implementation of Merdeka Belajar, Religious Attitudes